Analysis of Strengthening Bureaucracy Neutrality Policy Implementation in the Local Elections (A Study in North Sumatera) - Piki Darma Kristian Pardede; Rudi Kristian (Journal of Local Government Issues (LOGOS), 2021)
The issue of bureaucratic neutrality is a serious problem that continues to recur in implementing local elections (Pilkada) in Indonesia. Reflecting on what happened in the 2015 and 2017 North Sumatra Simultaneous Pilkada, this study aims to revive bureaucratic and political relations. Public services. This study uses a qualitative approach with data obtained through in-depth interviews with bureaucratic apparatus in the local government, The North Sumatera Election Provincial Commission (KPUD), The North Sumatera Election Supervisory Agency (Bawaslu), Independent Monitoring Institutions, Lecturer of Public Administration Universitas Sumatera Utara, observation and documentation. The results of this study emphasize the importance of State Civil Apparatus (ASN) to return to neutrality in increasing public trust in the bureaucracy. The results of this study emphasize the importance of ASN to return to neutrality in improving public confidence trust in the bureaucracy. This article argues for collaborative supervision conducted by various elements of government and society as an alternative strategic step to maintain the neutrality of State Civil Apparatus.